(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes modern innovative approaches and technologies in the field of museology of tangible cultural heritage objects. The study discusses such areas as 3D scanning (LiDAR, photogrammetry), virtual and augmented reality (VR/AR), the concept of a digital twin, FAIR data principles, and catalog systems based on artificial intelligence, based on an analysis of international and national scientific sources for 2020–2025. The article analyzes the task of digitizing 2.5 million museum objects within the framework of the “Uzbekistan — 2030” strategy and national practice using the example of the 360.vrmuseum.uz platform. The study evaluates the process of transition from the classical “object-showcase” model of museology to the “interactive experience ecosystem” from a philosophical and axiological point of view.